Analisis Parameter Particulate Matter 10 (PM10) pada Udara Ambien di Pasar Baruga Kota Kendari - Fabrianto, Muh Fadhlur; Ilham, Ilham; Sumarlin, Sumarlin (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
The problem of air pollution is a global problem that almost everyone experiences. Nearly 90% of people in the world live in an environment where the air is not healthy. One of the places that may affect the pollutant is, where the market has a level of crowd and traffic density that can have an impact on the environment. One of them is the central market of Kendari City.this study aims to determine the concentration of particulate matter (PM10) in the baruga market in kendari city and the amount of traffic volume at three predetermined times.the results obtained are the concentration of PM10 in ambient air in the baruga market, kendari city at three times, namely morning, afternoon and evening. 26,92 μg/Nm3 with a temperature of 33,5oC, in the afternoon the results obtained are 51,67 μg/Nm3 with a temperature of 35,25oC and in the afternoon the results are 18,50 μg/Nm3 with a temperature of 32,33oC which still meets the PP quality standard. No.41 of 1999.